Fostering students’ spatial ability in learning polyhedra using augmented reality-based android 3D interactive learning media - Anita Dewi Utami; Fathia Yasmin Aulia Rahma; Sinta Agustin Ningseh; Nur Ayufauziyah (CV. FOUNDAE, 2026)
Background: The low level of spatial ability is one of the main factors contributing to students’ difficulty in understanding geometry, particularly polyhedra. This difficulty is evident in recognizing shapes, visualizing shape transformations and rotations of objects, understanding the relationships between parts of an object, and determining the relative positions of objects Aims: The purpose of this study is to describe the process of developing a 3D interactive learning tool based on augmented reality for an Android app, featuring polyhedra content that supports the development of valid, practical, and effective spatial ability. Methods: This research method employs the Research and Development approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) proposed by Dick and Cary. Result: The results of this study show that in the needs and problem analysis phase, issues were identified through observation and interviews. The design phase included developing learning objectives, scenarios, media design, content, and assessment tools based on the analysis results. In the development stage, the initial design was transformed into a product validated by experts, achieving 78.4% from media experts and 78.8% from content experts. During implementation, the media was applied and obtained an 81.9% practicality rating and 81.25% effectiveness, indicating its effectiveness in enhancing students’ spatial ability in polyhedra material. The evaluation phase further analyzed student responses comprehensively. Conclusion: Based on this description, it can be concluded that the 3D Android application is valid, practical, and effective for use in learning.